Compet??ncias do secretariado executivo na gest??o de projetos socioambientais sob a perspectiva do gerente de projetos - Todorov, Maria do Carmo Assis (2015)
In the latest decades, the search for competitive advantage has driven organizations to focus on project management. To succeed in this endeavor it is necessary the development of project team competences. Communication hurdles and the needs for leadership in project management are the main reasons that compromise the project success. Like in project management, the executive secretary functions evolved up to acquire capabilities to contribute with new mechanisms/routines to improve project processes, including socio-environmental projects. Considering that executive Secretary is a reliable allied to improve project communication in project teams, this research concentrates on the analysis of project manager???s perception regarding the executive Secretary???s contributions to, socio-environmental project management. In order to assure the possibility to relate executive Secretary???s competences with project???s team competences, one used the list of competences from National Curriculum Guideline of executive Secretary Program and the set of competences proposed by the International Project Management Association, to build a theoretical model, that was evaluated through structural modeling equations. Results show that executive Secretary competences adhere and contribute to improve project team management, allowing for an effective socio-environmental project management. Therefore, project managers can use executive Secretary to boost project success. The study also show contributions to executive Secretary undergraduate programs, pinpointing which competences need a better attention for student???s professional profile development. Results also show that some competences needing improvement are acquired during the executive secretary professional formation, requiring, therefore, that practicing project executive secretaries do hold a major in executive secretary.